Effects of Metformin on Endocrine and Metabolic Parameters in Patients with Polycystic Ovary Syndrome - Zahra, M.; Shah, M.; Ali, A.; Rahim, R. (Hormone and Metabolic Research, 2017)
The present study was designed to evaluate the effects of metformin on metabolic and endocrine parameters in patients with polycystic ovary syndrome (PCOS). The study included 40 patients with PCOS. Patients were divided into 2 groups based on whether they will receive metformin (500 mg 3 times a day, n=20) or placebo (n=20) for 3 consecutive months. Serum concentrations of fasting blood glucose, insulin, HOMA-IR, INSL-3, visfatin, FSH, and LH were measured at baseline and after 3 months of therapy. The key endocrine and metabolic parameters significantly changed after metformin treatment. The systolic and diastolic blood pressures were significantly reduced in the metformin group after treatment compared to placebo (p<0.001). A significant reduction in the size of the right ovary was observed after metformin treatment (p=0.05), while no change was found in the size of left ovary (p>0.12). Moreover, a significant reduction was observed in the serum levels of FSH (p>0.01), LH (p>0.001), and visfatin (p>0.001) after metformin treatment. However, HOMA-IR (which is used to assess insulin resistance) failed to reach the statistical significance (p=0.20). We conclude that metformin treatment in females with PCOS showed significant improvement in systolic and diastolic blood pressures. In addition, an improvement in the hormonal profile in the form of reduction in LH, FSH, and visfatin levels was observed. Thus, therapeutic intervention with metformin could be of clinical importance in high-risk group of young females with PCOS.
Keywords: diabetes; polycystic ovary syndrome; metformin; insulin; INSL3; visfatin